2010
DOI: 10.1016/s0140-6736(10)60588-0
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic determinants of vitamin D insufficiency: a genome-wide association study

Abstract: Background-Vitamin D is crucial for maintaining musculoskeletal health. Recently, vitamin D insufficiency has been linked to a number of extraskeletal disorders, including diabetes, cancer, and cardiovascular disease. Determinants of circulating 25-hydroxyvitamin D (25-OH D) include sun exposure and dietary intake, but its high heritability suggests that genetic determinants may also play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,195
21
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,387 publications
(1,333 citation statements)
references
References 33 publications
78
1,195
21
10
Order By: Relevance
“…rs4588 in GC , rs10741657 in CYP2R1 and rs6013897 in CYP24A1 have been used in genetic instruments for 25OHD in MR studies before. rs4423214 near DHCR7 is in perfect LD with rs12785878, identified in the original SUNLIGHT consortium 25OHD GWAS 22. Finally, rs116970203 near CYP2R1 is a low frequency variant identified in the most recent GWAS of 25OHD and has been shown to act independently of rs10741657 23…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…rs4588 in GC , rs10741657 in CYP2R1 and rs6013897 in CYP24A1 have been used in genetic instruments for 25OHD in MR studies before. rs4423214 near DHCR7 is in perfect LD with rs12785878, identified in the original SUNLIGHT consortium 25OHD GWAS 22. Finally, rs116970203 near CYP2R1 is a low frequency variant identified in the most recent GWAS of 25OHD and has been shown to act independently of rs10741657 23…”
Section: Methodsmentioning
confidence: 88%
“…Common genetic variants have been identified in Genome Wide Association Studies (GWAS)21, 22 of 25OHD, only variants that passed a genome wide association threshold ( p  < 5 × 10 −8 ) and had been replicated were selected. These genetic proxies or instruments are located in or near four 25OHD related genes: Group‐specific component ( GC ), cytochrome P450 family 2, subfamily R, polypeptide 1 ( CYP2R1 ), 7‐dehydrocholesterol reductase ( DHCR7 ) and cytochrome P450, family 24, polypeptide 1 ( CYP24A1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the result of a large genome wide association study on 33,996 individuals demonstrated the association of variants at three loci with lower 25-OH vitamin D concentrations [23]. However, as pointed out in an accompanying editorial, the "battle" against vitamin D deficiency is not likely to be affected by these findings [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in genetic testing have permitted, via genome-wide association studies (GWAS), the identification of various single nucleotide polymorphisms (SNPs) in genes encoding proteins involved in vitamin D synthesis, transport and metabolism, that are associated with circulating levels of 25(OH)D (75,76). Genes included in the results of the GWAS were 7-dehydrocholesterol reductase (DHCR7), CYP2R1, 1,25-dihydroxyvitamin D-24-hydroxylase (CYP24A1), and vitamin D binding protein (GC).…”
Section: Novel Perspectives I Genetic Variants In Vitamin D Homeostamentioning
confidence: 99%